The implementation and challenges of breastfeeding counselling program in Majene district, West Sulawesi: A qualitative study among health workers - Febriyanti, Dyah; Februhartanty, Judhiastuty; Wiradnyani, Luh Ade Ari (World Nutrition Journal, 2025)
Background: Inadequate breastfeeding practices increase the risk of malnutrition, infant deaths, and other related developmental problems. Counselling on breastfeeding promotion is one of the most effective ways to improve breastfeeding practices. Nevertheless, challenges in implementing the counselling hinder its effectiveness. Using the logic model framework, this study examines the implementation and challenges of breastfeeding counselling programs in Majene District, West Sulawesi Objective: This study aims to gain an in-depth understanding of experiences and perspectives regarding the implementation of the breastfeeding counselling program using the Logic Model among health workers in Majene District. Methods: From January to June 2024, a qualitative phenomenological approach was employed. Data collection included in-depth interviews with 12 trained breastfeeding counsellors, eight key informants, and focus group discussions with 24 mothers. Thematic analysis using NVivo 12, guided by the Logic Model framework, which grouped breastfeeding counselling into input, process, outputs, and outcomes aspects. Results: Key challenges included a shortage of trained counsellors, limited infrastructure, and budget constraints. Health workers adapted by integrating counselling into maternal health services, conducting home visits, and collaborating with Posyandu cadres. Exclusive breastfeeding rates showed slight improvements but remained below national targets. Beneficiaries expressed satisfaction but highlighted the need for longer and more frequent counselling sessions. Conclusions: The program faced significant resource challenges, including a shortage of skilled counsellors, budget constraints, and limited facilities. However, adaptive strategies by health workers crucial for overcoming logistical and resource constraints resulted in beneficiaries’ satisfaction and positive developments in breastfeeding rates.